Doktrin Gereja (Ekklesiologi): Sebuah Kajian Literatur - Dina Radina Singal; Eny Emelia Hewuni; Eka Andika Saputra; Sarmauli (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
This article discusses how church doctrine relates to the church, where the church, as the body of Christ, is inseparable from the fundamental teachings of its faith and confession. Doctrine is a crucial foundation that supports church life. In the New Testament, the word ekklesia refers to